Self-assessment of strength abilities in climbing: Impact of skill level - Carla Zihlmann; Paul Ritsche; Martin Keller; Daniel Zobrist; Lisa Reissner; Peter Wolf (Bern Open Publishing, 2024)
Introduction Many climbers believe that they are stronger in crimp finger position than in open hand position. However, compared to open hand, crimped fingers are associated with higher pulley forces increasing the risk of injuries. Climbing expertise may influence the estimation of strength, i.e., the better the climber, the better the self-assessment. This study therefore aimed to find out whether climbing expertise influences self-assessment of finger flexor strength in half-crimp and in open hand position. Methods Data was collected at the Hands-On Science Booth of the Climbing World Championships in Bern. Participants had to fill out a questionnaire including a self-assessment of their climbing expertise and of their maximum finger strength for both hands as well as both finger positions. Afterwards, maximum finger strength was measured on an instrumented campus board: Participants placed the to-be-measured hand on a self-selected rung (depth of 23 mm) and then tried to transfer as much force as possible from their feet to their fingers. Results The analysis was based on 38 intermediate and 36 advanced climbers. Due to the limited number of participants in the lower grade (n = 0) and elite (n = 2) level, those skill levels were not considered. Advanced climbers generated significantly greater forces than intermediate climbers across all four measured conditions (t-tests, all p < 0.01). For both groups, neither in the dominant nor in the non-dominant hand a significant difference in maximum force was observed, e.g., dominant hand, intermediates:  or advanced climbers: . Intermediate climbers did neither over- nor underestimate their strength in half-crimp position compared to open hand (paired t-test, p = 0.91 for dominant, p = 0.077 for non-dominant hand). In contrast to the dominant hand, advanced climbers significantly overestimated their strength in half-crimp position for the non-dominant hand (on average 9%, Cohen's d 0.64, p < 0.01). Discussion/Conclusion Our results confirm the positive correlation between finger strength and climbing level. We also confirm that on a 23 mm rung, greater forces can be generated with in open hand compared to half-crimp (Winkler et al., 2023). With larger hold depths, force generated in open hand significantly increases (Amca et al., 2012), while for smaller holds, force exerted in half-crimp position exceeds that of open hand (Winkler et al., 2023). Hence, at least for larger holds, we recommend adopting an open hand position as preventive measure against finger injuries. Advanced climbers may tend to inaccurately self-assess their strength due to their greater engagement with peers, potentially leading to the circulation of misinformation. Note that participants were instructed to provide a general self-assessment of their strength rather than for a 23 mm deep rung, i.e., they may have had a smaller hold in mind. References Amca, A. M., Vigouroux, L., Aritan, S., & Berton, E. (2012). Effect of hold depth and grip technique on maximal finger forces in rock climbing. Journal of Sports Sciences, 30(7), 669-677. https://doi.org/10.1080/02640414.2012.658845 Winkler, M., Künzell, S., & Auguste, C. (2023). Competitive performance predictors in speed climbing, bouldering, and lead climbing. Journal of Sport Sciences, 41(8), 736-746. https://doi.org/10.1080/02640414.2023.2239598